2021
DOI: 10.1007/s40119-021-00242-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dapagliflozin on Platelet Function Testing Profiles in Diabetic Patients: The EDGE Pilot Study

Abstract: Introduction: This prospective pharmacodynamic (PD) study assessed the effect of the sodium-glucose co-transporter-2 inhibitor (SGLT2i), dapagliflozin, on platelet reactivity. Methods: Patients with stable coronary artery disease (CAD) and type 2 diabetes mellitus (T2DM) (n = 27) who were on maintenance dual antiplatelet therapy (DAPT) of aspirin 81 mg daily, and clopidogrel 75 mg daily were recruited. Platelet function was evaluated with the VerifyNow TM P2Y 12 assay (Werfen, Bedford, MA, USA) and assessed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…This result shows that dapagliflozin treatment has obvious clinical benefits in BMI, lowering blood pressure, and controlling blood sugar, but there is no apparent advantage in blood lipids. In previous foreign studies [20,21], some scholars found that dapagliflozin treatment can reduce systolic blood pressure by 11.9 mmHg, which is close to the results of this study. The production of adipokines is a common mechanism of cardiovascular disease and insulin resistance, and ectopic fat deposition in the perivascular and epicardium significantly affects the paracrine process of myocardial adipokines [22].…”
Section: Discussionsupporting
confidence: 91%
“…This result shows that dapagliflozin treatment has obvious clinical benefits in BMI, lowering blood pressure, and controlling blood sugar, but there is no apparent advantage in blood lipids. In previous foreign studies [20,21], some scholars found that dapagliflozin treatment can reduce systolic blood pressure by 11.9 mmHg, which is close to the results of this study. The production of adipokines is a common mechanism of cardiovascular disease and insulin resistance, and ectopic fat deposition in the perivascular and epicardium significantly affects the paracrine process of myocardial adipokines [22].…”
Section: Discussionsupporting
confidence: 91%
“…Dapagliflozin is a class of hypoglycemic agents that has received considerable attention in recent years [3,4]. It lowers blood glucose and blood pressure, ameliorates blood lipids, and provides cardioprotective effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this study being sufficiently powered for prospective pharmacodynamic outcomes with respect to PRUs and ARUs, it was not designed for prespecified clinical outcomes, and thus no definitive conclusions on clinical efficacy and safety can be ascertained. As with previous studies conducted by this group in Trinidad, there was a preponderance of South Asian patients, alluding to a selection bias during study enrolment 14 43. A double-blind, randomised controlled trial would have been the gold standard for ascertaining the antiplatelet effect of this cocoa intervention; however, there are logistical challenges in executing such methodology in our limited resource setting without a dedicated clinical research organisation 44…”
Section: Discussionmentioning
confidence: 91%